Comparing Some Methods of Estimating the Parameters and Survival Function of a Log-logistic Distribution with a Practical Application - al-aameri, Samah Sabah Hassan; AL.Doori, Entsar Arebe Fadam (Journal of Economics and Administrative Sciences, 2022)
The Log-Logistic distribution is one of the important statistical distributions as it can be applied in many fields and biological experiments and other experiments, and its importance comes from the importance of determining the survival function of those experiments. The research will be summarized in making a comparison between the method of maximum likelihood and the method of least squares and the method of weighted least squares to estimate the parameters and survival function of the log-logistic distribution using the comparison criteria MSE, MAPE, IMSE, and this research was applied to real data for breast cancer patients. The results showed that the method of Maximum likelihood best in the case of estimating the parameters of the distribution and survival function